Effects of biofertilizer rates on the structural, morphogenetic and productive characteristics of Piatã grass - Orrico Junior, Marco Antonio Previdelli [UNESP]; Centurion, Stanley Ribeiro; Amorim Orrico, Ana Carolina; da Silva Sunada, Natália (FapUNIFESP (SciELO), 2012)
The objective of this study was to investigate the influence of different levels of biofertilizers from cattle and swine manure on the structural, morphogenetic and productive characteristics of Brachiaria brizantha cv. Piatã. The experiment was arranged in a completely randomized factorial design with split plots. The plots were defined by eight treatments: two biofertilizers (cattle and swine), four levels (0, 100, 200 and 300 kg N.ha -1) and subplots by four different cutting periods. The cutting for plant uniformity was performed at 45 days after sowing at 15 cm above the soil surface. The biofertilizeres were applied in a single level, after the cutting of plants, in rates of 0, 0.23 and 0.19, 0.45 and 0.38, 0.68 and 0.57 liters pot -1 for the biofertilizers from cattle and swine manure, respectively. These rates were also equivalent to levels of 0, 100, 200 and 300 kg N.ha -1. There was no significant difference between the types of biofertilizers as there was no interaction between them and the different levels, hence both biofertilizers could be applied without any loss of nutrient intake by the plants used in this experiment. There was a significant difference between the production of green and dry matter, the leaf appearance rate, phyllochron, leaf and pseudostem elongation rates, number of green leaves, final leaf length, number and weight of tillers, according to the increase of nitrogen rates, following linear prediction model. Effect of the cutting periods was also observed, once the plants harvested during the summer presented greater performance of structural and morphogenetic characteristics. © 2012 Sociedade Brasileira de Zootecnia.
Keywords: Brachiaria brizantha; Forage production; Organic fertilizer; Phyllochron